Application of generalized lambda distribution for unimodal data - PRAJNESHU, PRAJNESHU; GHOSH, HIMADRI (The Indian Journal of Agricultural Sciences, 2011)
Pearsonian system of curves has been widely used to obtain the probability distribution of unimodal data sets. However, its main limitation is that each family requires different functional forms, which may be troublesome to implement especially on the boundaries between families. To this end, the purpose of this paper is to bring to the notice of Agricultural Scientists the existence of a very versatile family of generalized lambda distributions (GLD). A brief description is also provided of the recently developed GLDEX package, Ver. 1.0.3 in R, Ver. 2.8.1 software to fit GLD to data. An attractive feature of this software package is that it is freely downloadable. As an illustration, the probability density function of monthly rainfall data for Assam and Meghalaya meteorological subdivision is obtained.